Exploring the Effect of the Use of Artificial Intelligence (AI) Based Learning Media on the Self-Confidence of History Education Students in Microteaching Practice - Isna Isna (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This study aims to explore the influence of the use of Artificial Intelligence (AI)-based learning media on students' self-confidence in microteaching practice. This research is based on the increasingly widespread use of AI in the learning process, particularly as a tool for teaching preparation, classroom simulations, and teaching performance evaluation. This study uses qualitative research methods with a qualitative descriptive approach to answer the research questions by describing the Microteaching learning activities and measuring the effectiveness of prospective history teachers' competencies. The results of this study indicate that the use of AI-based learning media positively contributes to increasing student self-confidence. This influence is evident in students' ability to prepare teaching materials more effectively, simulate material delivery, and receive rapid and accurate feedback on their teaching performance. Furthermore, AI helps students reduce anxiety, improve communication clarity, and build self-awareness of weaknesses and potential improvements. This study recommends more systematic integration of AI training into microteaching to support the improvement of pedagogical competence and self-confidence of prospective educators.